Toxoplasmosis in at-risk groups of patients. Issue 1 (January 2016) - Kucerova, Petra; Cervinkova, Monika
Abstract : Toxoplasmosis, one of the most common parasitic zoonoses worldwide caused by the protozoan Toxoplasma gondii, is found all over the world, and can affect any warm-blooded animal, including humans, although the primary host is the cat. Disease transmission occurs from eating undercooked lamb, beef or pork, ingestion of soil, drinking contaminated water, those undergoing blood transfusion or organ transplantation, transplacental transfer from mother to foetus and during careless handling of cat litter. The highest prevalence (about 55%) in Europe is seen in France and Greece. Toxoplasmosis is usually asymptomatic or is characterized by mild flu-like symptoms in healthy people. Pregnant women and immunosuppressed patients (HIV/AIDS patients) may develop serious health problems. Symptomatic patients usually suffer from malaise, headache, low-grade fever and cervical lymphadenopathy, but in severe cases, there can be manifestations such as encephalitis, myocarditis or hepatitis. In immunosuppressed patients testing positive for the parasite, there is risk of reactivation of infection. In these persons, it is recommended that biological specimens are examined using PCR or histological staining; in a case of central nervous system infection, detection of parasite DNA in brain biopsies using molecular biological methods. Toxoplasmosis acquired during pregnancy means high risk of damage for the foetus. It is necessary to determine whether the infection was received before or after pregnancy began. Paediatric toxoplasmosis can either be congenital or postnatally acquired; although little is known about postnatally acquired toxoplasmosis, congenital toxoplasmosis can be the consequence of transplacental haematogenous infection of the foetus during primary infection of the pregnant woman.